Pemikiran fikih : H. Abdul Rani Mahmud (1912-1993) - Rahmatullah, Muhammad (Pontianak : STAIN Pontianak Press, 2013)
H. Abdul Rani Mahmud, an ulama from West Kalimantan; his thoughts on fiqh.
Daftar pustaka : mukasurat 87-91.
Keywords: Mahmud, H. Abdul Rani, -- 1812-1993 -- Views on Islamic law; Ulama -- Indonesia -- Kalimantan Barat